Cellulose oxygen isotopes at Sites MHWL-1 and MHWL-3 - Masanobu Yamamoto; Osamu Seki (PANGAEA, 2022)
In Hokkaido, northern Japan, densely populated societies of hunter-fisher-gatherer cultures persisted over the Holocene until the 19th century. We used the cellulose δ18O values of Sphagnum and vascular plants in peat cores from Rishiri Island to understand paleoclimate changes in Hokkaido over the past 4400 years and discuss the impacts of climate changes on the development of the cultures. The cellulose δ18O values showed multi-centennial and millennial variations, reflecting the intensity of the Tsushima Warm Current and the summer position of the westerly jet. The marine hunter-fisher cultures responded to changes in the strength of Tsushima Warm Current and coastal primary production. In contrast, the inland cultures responded to changes in the latitudinal position of the summer westerlies. This implies that human societies of different lifestyles responded differently to climate changes.